Foamy virus–mediated gene transfer to canine repopulating cells - Kiem, Hans-Peter (American Society of Hematology, 2007)
Foamy virus (FV) vectors are particularly attractive gene-transfer vectors for stem-cell gene therapy because they form a stable transduction intermediate in quiescent cells and can efficiently transduce hematopoietic stem cells. Here, we studied the use of FV vectors to transduce long-term hematopoietic repopulating cells in the dog, a clinically relevant large animal model. Mobilized canine peripheral blood (PB) CD34(+) cells were transduced with an enhanced green fluorescent protein (EGFP)–expressing FV vector in an 18-hour transduction protocol. All 3 dogs studied had rapid neutrophil engraftment to greater than 500/μL with a median of 10 days. Transgene expression was detected in all cell lineages (B cells, T cells, granulocytes, red blood cells, and platelets), indicating multilineage engraftment of transduced cells. Up to 19% of blood cells were EGFP(+), and this was confirmed at the DNA level by real-time polymerase chain reaction (PCR) and Southern blot analysis. These transduction rates were higher than the best results we obtained previously with lentiviral vectors in a similar transduction protocol. Integration site analysis also demonstrated polyclonal repopulation and the transduction of multipotential hematopoietic repopulating cells. These data suggest that FV vectors should be useful for stem-cell gene therapy, particularly for applications in which short transduction protocols are critical.